Urban Metabolism of Intermediate Cities: The Material Flow Analysis, Hinterlands and the Logistics‐Hub Function of Rennes and Le Mans (France) - Bahers, Jean‐Baptiste; Barles, Sabine; Durand, Mathieu (Journal of industrial ecology, 2019)
Summary Although urban metabolism has been a subject of renewed interest for some years, the related studies remain fragmented throughout the world. Most of them concern major cities (megacities and/or national capitals) and, more rarely, intermediate, medium‐sized or small cities. However, urbanization trends show that together with the metropolization process, another one is characterized by the proliferation of intermediate cities. We have studied the metabolism of two French intermediate cities for the year 2012: Rennes Métropole (400,000 inhabitants) and Le Mans Métropole (200,000 inhabitants). To this end, we used material flow analysis (MFA) based on the methodology developed by Eurostat, adapted to the subnational level. This has been made possible by the use, for the first time, of very precise statistical sources concerning freight. We have developed a multiscale approach in order to weigh the urban metabolism of those two cities and to compare it to other cases and larger territories. This allows a better understanding of the specific territorial metabolism of intermediate cities, their hinterlands, and their logistics‐hub function. We conclude with the “urban dimension” of social metabolism, and, thanks to the multiscale approach, to the debate regarding logistical hubs, dematerialization, and territorial autonomy.